Travel-associated sexually transmitted infections in Japan: An observational study using imported infectious disease registry data - Konishi, Keiji; Kutsuna, Satoshi; Yamamoto, Kei; Nomoto, Hidetoshi; Shirano, Michinori; Yamato, Masaya; Yoshimura, Yukihiro; Sakamoto, Naoya; Nagasaka, Atsushi; Ohmagari, Norio (Global Health & Medicine, 2024)
International travel is a risk factor for acquiring sexually transmitted infections (STIs) owing to factors such as increased sexual opportunities, a sense of freedom, and the allure of the sex industry. We investigated the incidence of travel-associated STIs in Japan using data from the Japan Registry for Infectious Diseases from Abroad (J-RIDA) reported by 17 participating medical institutions between October 2017 and December 2022. Data were collected on the patients' age, sex, nationality, chief complaint, whether they had visited a travel clinic before travel, travel history, and final diagnosis. Of 4545 cases of travel-associated illness reported, 52 (1.1%) were STIs. Most patients with STIs were male (81%) with a median age of 31 years. HIV (17%), genital herpes (13%), syphilis (13%), and gonorrhea (12%) were the most frequently reported STIs. Only one patient had visited a travel clinic before travel. Promoting awareness and vaccination is crucial for preventing travel-associated STIs.